ELISA indireto para detecção de Ig G anti-vírus da doença de newcastle em soro de codorna - Daniela Duarte de Oliveira (2004)
Two indirect ELISA's one containing secundary antibody against quail lgG and the other one conjugated anti-chicken lgG, were developed and compared for the detection of quail (Coturnix cortunix japonica) lgG specific to Newcastle disease virus (NDV). For the production of secindary antibody (mice lgG anti-quail lgG), purification methods of quail lgG were evaluated using 30 quail serum and egg yolk samples confirmed by electrophoresis. Only lgG purified from serum due to its higher purity were inoculated in to mice in oil emulsion containing 50ug protein/dose for the production of secondary antibody. Thirty positive quail serum against NDV and 30 negative serum previously tested by the haemaglunation inhibition test (HI) were used in the block standardization of ELISA. The NDV, positive and negative serum, secondary antibody and conjugates (goat anti-mouse lgG and rabbit anti-chicken lgG conjugated with alkaline phosphatase were diluted serially to standardized the indirect ELISA to detect quail lgG against NDV and indirect ELISA to detect quail lgG against NDV using anti-chicken conjugated. The absorbance values from both ELISA were evaluated in a TG-ROC spreadsheet and the cut-off points were determined to each ELISA. Based on the results it was observed a total correlation between ELISA an IH test, used as gold test. Both Elisa were efficient on positive and negative serum identification, presenting highest values of sensibility and specificity (100%) without false-positive and false-negative results. These results indicate the use of indirect ELISA to Newcastle disease as an excellent test to detect antibody in quail serum and your use in a laboratory routine.